Dynamic behavior of the coffee fruit-stem-branch system using Stochastic finite element method - Coelho, Andre Luiz de Fretas; dos Santos, Fábio Lúcio; de Queiroz, Daniel Marçal; Pinto, Francisco de Assis de Carvalho (Coffee Science - ISSN 1984-3909, 2016)
The development of an efficient machine for harvesting coffee requires comprehensive knowledge of the dynamic behavior of the plant and its parts. The finite element method is a numerical approach used to determine natural frequencies and mode shapes. However, the stochastic finite element method has not been employed for the analysis of the dynamic behavior of coffee. The aim is to determine the natural frequencies and mode shapes for the coffee fruit-stem-branch system. The natural frequencies and the mode shapes were determined by employing the stochastic finite element method, in which the elastic modulus and the specific mass were treated as random variables, and the variation in the natural frequency was obtained as a function of the variability of these properties. The natural frequencies were reduced according to the evolution of the ripening process of the fruit and stem or due to the increase in the total weight of the system due to an increase in the number of fruits attached to the stem. The natural frequencies increased with an increase in the elastic modulus or with a reduction in the specific mass.